Goal setting in group programmes for long-term condition self-management support: experiences of patients and healthcare professionals. Issue 1 (2nd January 2020) - Hughes, Stephen; Lewis, Sophie; Willis, Karen; Rogers, Anne; Wyke, Sally; Smith, Lorraine
Abstract: Objective: To examine group facilitators' and participants' experiences of and engagement with goal setting in long-term condition (LTC) self-management group programmes. Design: We conducted a qualitative mixed method study including 13 interviews with group facilitators, 20 interviews with group participants and content analysis of programme workbooks. Participant interviews explored their goals for managing their condition. Facilitator interviews explored their goals for participants. Data from the three sources were analysed inductively and thematically. Results: The three themes showed: 1. Participants have personal and meaningful biomedical, social and emotional goals and, facilitators believe these goals to be important and perceive them as integral to increasing motivation and self-responsibility; 2. Facilitators shape participants' goals into pre-determined health behaviour change activities, disregarding social and emotional aspects; and 3. Participant disengagement from the goal setting process and questioning of the value of goal setting was evident. Conclusions: Patient engagement with goal setting may be less attainable when what matters to people is sidelined to focus on behaviour change goals and self-responsibility. Yet, supporting people to identify and pursue meaningful goals for living with LTCs is more likely to increase engagement and motivation. Stakeholders in group programme development and delivery should review their goal setting activities.